Taxes and employment subsidies in optimal redistribution programs - Beaudry, Paul; Blackorby, Charles 1937- (1998)
This paper characterizes an optimal redistribution program when taxation authorities: (1) are uninformed about individuals value of time in both market and non-market activities observe both market-income and time allocated to market employment, and (3) are utilitarian. Formally, the problem is a special case of a multidimensional screening problem with two dimensions of unobserved attributes. In contrast to much of the optimal income taxation literature, we show that optimal redistribution in this environment involves distorting market employment upwards for low net-income individuals (through negative marginal income taxes or employment subsidies) and distorting employment downward for high net-income individuals (through positive marginal income taxes). It is also shown that workfare is only part of an optimal program if certain individuals have not access to market employment.
Keywords: Impôt sur le revenu; Inkomensverdeling; Inkomstenbelasting; Subventions à l'emploi; Employment subsidies; Income tax